Stylus ion trap for enhanced access and sensing - Leuchs, Gerd; et al. (Nature Physics, 2009)
Small, controllable, highly accessible quantum systems can serve as probes at the single-quantum level to study a number of physical effects, for example in quantum optics or for electric- and magnetic-field sensing. The applicability of trapped atomic ions as probes is highly dependent on the measurement situation at hand and thus calls for specialized traps. Previous approaches for ion traps with enhanced optical access included traps consisting of a single ring electrode or two opposing endcap electrodes. Other possibilities are planar trap geometries, which have been investigated for Penning traps and radiofrequency trap arrays. By not having the electrodes lie in a common plane, the optical access can be substantially increased. Here, we report the fabrication and experimental characterization of a novel radiofrequency ion trap geometry. It has a relatively simple structure and provides largely unrestricted optical and physical access to the ion, of up to 96% of the total 4 solid angle in one of the three traps tested. The trap might find applications in quantum optics and field sensing. As a force sensor, we estimate sensitivity to forces smaller than 1 yN Hz 1/2. © 2009 Macmillan Publishers Limited.
UnivIS-Import:2015-03-09:Pub.2009.nat.dphy.optik.1optik.stylus